A Synthetic Route to Quaternary Pyridinium Salt-Functionalized Silsesquioxanes - Nataliya Kostenko; Jochen Gottfriedsen; Liane Hilfert; Frank T. Edelmann (International Journal of Polymer Science)
A synthetic route to potentially biocidal silsesquioxanes functionalized by quaternary pyridinium functionalities has been developed. N-Alkylation reactions of the precursor compounds 4-(2-(trimethoxysilyl)ethyl)-pyridine (5) and 4-(2-trichloro-silylethyl)pyridine (6) with iodomethane, n-hexylbromide, and n-hexadecylbromide cleanly afforded the corresponding N-alkylpyridinium salts (7–10). The synthesis of a 4-(2-ethyl)pyridine POSS derivative (2) was achieved by capping of the silsesquioxane trisilanol Cy7Si7O9(OH)3 (1) via two different preparative routes. Attempts to use compound 2 as precursor for quaternary pyridinium salt-functionalized POSS derivatives were met with only partial success. Only the reaction with iodomethane cleanly afforded the new N-methylpyridinium salt 12 in high yield, whereas n-hexylbromide and n-hexadecylbromide failed to react with 2 even under forcing conditions.